Tree communities and floristic composition of freshwater swamp forest remnants in Perak - Liliwirianis N.,; Mohd Nazip Suratman, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Much areas of freshwater swamp forest in Malaysia have been developed into urban settlement leaving small fragments of isolated habitat. This study was conducted to determine the plant communities and floristic composition of freshwater swamp forest in Universiti Teknologi MARA (UiTM), Sri Iskandar, Perak. A total of 17 plots measuring at 20 m × 20 m (0.68) ha were established in the study area. A total of 575 trees with diameter breast height (dbh) > 5 cm were enumerated, which gives tree density estimates of 845 trees ha-1. Floristic composition of tree communities at the study area comprises of 165 species, 88 genera and 36 families. Olacaceae is the most specious family, whereas the most dominant species is Nephelium costatum Hiern with an Importance Value Index (IVi) of 17.75%. Total tree basal area (BA) was 22.14 m2 ha-1. The Shannon- Weiner diversity index (H’) for the study is 1.15 (H’max = 6.35). Findings from this study may contribute in identifying species of special concerns results from freshwater swamps forest habitat fragmentation.